Validating the Clinical Use of the Modified Huddart and Bodenham Scoring System for Outcome in Cleft Lip and/or Palate. (November 2015) - Dobbyn, Lorna; Gillgrass, Toby; McIntyre, Grant; Macfarlane, Tatiana; Mossey, Peter
Objective: The aim of this study was to validate the clinical use of the modified Huddart and Bodenham scoring system for the measurement of maxillary arch constriction in children born with cleft lip and/or palate. Design: The study design consisted of a reliability assessment between clinical and study model scoring. Setting: The study was carried out in cleft clinics at three hospital-based orthodontic units. Participants: A total of 53 subjects were recruited when attending routine clinic appointments and gave informed consent to participate. Intervention: The modified Huddart and Bodenham scoring system was applied to study models for 53 subjects by all examiners; whereas, one examiner scored 53 subjects clinically, the other two examiners scored 25 and 28 subjects, respectively, on two occasions at least 1 month apart. Main Outcome Measure: Reliability of modified Huddart and Bodenham scoring clinically and on study models was compared. Results: When scoring clinically with the modified Huddart and Bodenham index on two occasions, the intraexaminer and interexaminer intraclass correlation coefficients (ICC) indicated a high level of repeatability and reliability (ICC range, 0.941 to 0.989). The Bland-Altman plots did not show any areas of systematic bias. The ICC between clinical and model scores for each examiner ranged between 0.923 and 0.959. The Bland-Altman plots did not show any areas of systematic bias. The ICC between clinical and model scores for each examiner ranged between 0.923 and 0.959. Canines had lower reliability than molars and incisors. Conclusions: There was excellent intraexaminer and interexaminer agreement both on study models and in the intraoral scoring using the modified Huddart and Bodenham index. In addition, there was a high degree of correlation between study model and clinical scores using this index.